Pediatric to adult care transfer in rare liver diseases: Recommendations based on insights from a European omnistakeholder event - Karsten Vanden Wyngaert; Janne Suykens; Deirdre Kelly; Isabel Goncalves; Ena Lindhart Thomsen; Jose Willemse; Zoe Mariño; João Madaleno; Jemma Day; Marianne Samyn; Mohamed Ali; Marianne Hørby Jørgensen; et al. (JHEP Reports)
Background & Aims: The transfer journey from pediatric to adult care services of young people with rare liver diseases poses significant challenges and is an underexplored research area. This study examined the critical aspects of, and opportunities for, transfer journey management for these young people in Europe. Methods: In total, 72 individuals, representing 13 countries, participated in an omnistakeholder workshop on 17–18 March 2023. A standardized workshop methodology was used to discuss critical aspects and actions over nine focus sessions. The themes of these sessions were identified by engaging with healthcare providers, young people, and parents. Results (i.e. aspects receiving >25% of the votes) were ranked based on importance and validated by the European Reference Network of Hepatological Diseases (ERN RARE-LIVER) youth panel. Results: Our findings revealed that the critical aspects of transfer journey management predominantly revolved around the transfer itself. Most of the critical aspects and actions were related to improving communication (e.g. allocating sufficient time, 81% of votes; giving consistent information, 43%; and discussing communication preferences, 100%), relational continuity (e.g. appointing a transition person to liaison between stakeholders, 79%), and management continuity (e.g. using a transfer document, 60%). Our results also underscored the importance of peer mentorship programs (100%), informing young people about the transfer process (85%), and implementing joint consultations (93%). Conclusions: Current literature and guidelines on ‘transition’ might not fully address real-world challenges in rare liver diseases, particularly those concerning maintaining continuity of care during the actual transfer process. Future research should examine the effectiveness of strategies aimed at enhancing communication and continuity of care throughout the transfer journey, focusing on stakeholder experience. Impact and implications: This international omnistakeholder workshop explored challenges and opportunities in managing transfer journeys for young people with rare liver diseases. By emphasizing practical implications (leading to actions), it provides a benchmark for improving transfer journeys worldwide, applicable to not only rare liver diseases, but possibly also common liver or other rare diseases. Our findings underscore the fundamental importance of the transfer itself in maintaining continuity of care. The critical aspects identified center around informative, relational, and management continuity of care and have been transformed into minimal criteria.